Functional redundancy of the premotor network in hemispherotomy patients - Conrad C. Prillwitz; Bastian David; Gottfried Schlaug; Thomas Deller; Johannes Schramm; Robert Lindenberg; Elke Hattingen; Bernd Weber; Rainer Surges; Christian E. Elger; Theodor Rüber (Annals of Clinical and Translational Neurology, 2021)
Abstract Objective Using multimodal imaging, we tested the hypothesis that patients after hemispherotomy recruit non‐primary motor areas and non‐pyramidal descending motor fibers to restore motor function of the impaired limb. Methods Functional and structural MRI data were acquired in a group of 25 patients who had undergone hemispherotomy and in a matched group of healthy controls. Patients’ motor impairment was measured using the Fugl‐Meyer Motor Assessment. Cortical areas governing upper extremity motor‐control were identified by task‐based functional MRI. The resulting areas were used as nodes for functional and structural connectivity analyses. Results In hemispherotomy patients, movement of the impaired upper extremity was associated to widespread activation of non‐primary premotor areas, whereas movement of the unimpaired one and of the control group related to activations prevalently located in the primary motor cortex (all p ≤ 0.05, FWE‐corrected). Non‐pyramidal tracts originating in premotor/supplementary motor areas and descending through the pontine tegmentum showed relatively higher structural connectivity in patients (p < 0.001, FWE‐corrected). Significant correlations between structural connectivity and motor impairment were found for non‐pyramidal (p = 0.023, FWE‐corrected), but not for pyramidal connections. Interpretation A premotor/supplementary motor network and non‐pyramidal fibers seem to mediate motor function in patients after hemispherotomy. In case of hemispheric lesion, the homologous regions in the contralesional hemisphere may not compensate the resulting motor deficit, but the functionally redundant premotor network.